A simplified method for mandibular repositioning using acrylic bone cement during segmental mandibulectomy - KAWAI, Tosihiko; HACHIYA, Hiroshi; SHIROZU, Takamasa; NARITA, Takanori; IKE, Masao; MIYACHI, Hitoshi (Japanese Journal of Oral and Maxillofacial Surgery, 1996)
Loss of mandibular continuity due to segmental mandibulectomy leads to esthetic and functional problems. Restoration of mandibular continuity after segmental mandibulectomy is one of the chalenges of reconstructive surgery. In this paper, a simple technique is described which utilizes acrylic bone cement for a template of the mandible. Before mandibular resection, mandibular continuity is restored with soft acrylic bone cement contained in a flexible tube. The tube is attached to residual sites with small monocortical screws. The tube is held until the cement solidifies. When the bone cement has hardened, the tube can be removed. After mandibular resection, the tube is replaced to realign the mandibular segment and correctly restore the patient's occlusion and facial esthetics.